HİLAL-İ AHMER TEŞKİLATININ KURULUŞU VE TEŞKİLATLANMASI - POLAT, MEHMET (Fırat Üniveristesi, 2007)
Bu tez Avrupa'da XIX. yüzyı kurulmuş uluslar arasılda ilk yardı kurumu Kılhaç'ım zı nOsmanlıDevletindeki yansımasıolan Kılay teş nı kuruluş ve ilk faaliyetlerinizı kilatın unuincelemektedir. Cemiyet dönemin önde gelen aydınları devlet adamaları n buluş u birve nı tuğıkurum olarak karş za çımı kmaktadı Kuruluşr. unun üzerinden fazla zaman geçmemesinerağmen OsmanlıDevletinin girdiğ büyük savaşi larda devletine ve milletine çok büyükyardımlarıolan bu kurumun kı sürede güçlenmesinin ve halk tarafısa ndan özümsenmesininardı yatan gerçek halkı devlet ve milletine olan borcunu ödeme düşnda n üncesinin Hilal-iAhmer Cemiyeti içinde hayat bulmuşolması r.dı

The Red Cross, which was established in the XIX. Century Europe was the world fisthumanitarian organisation. This thesis is about the establishment and the first years of TheOttoman Red Crescent, which was formed as a counterpart to the Red Cross. The organisationincluded, outstanding members of the society such as intellectuals and government officials.Although short after its establishment the organisation was put to test by the great wars theEmpire entered and proved to be very efficient at helping the country and nation. Theorganisation grew strong with the support of the nation, the reason of this success could bethat the people saw the organisation a way to pay their dept to the country.
The establishment and organization of the Ottoman red crescent
Keywords: Tarih